Dynamics of Some Medical and Demographic Indicators in St. Petersburg During the Period from 2018 to 2023 - Anatoly S. Simakhodsky; Ludmila D. Sevostyanova; Yulia V. Lukashоva; Natalya V. Petrova; Oleg A. Simakhodsky ("Paediatrician" Publishers LLC, 2024)
Background. There have been negative trends in the birth rate and population growth decline in recent years. Forecasts from demographers are also not so encouraging as the next generation of childbearing age is one from the end of the last century which is characterized by low birth rate. Population mortality exceeded the birth rate during the years of challenging and questionable economic reforms. Moreover, there was a high level of chronic morbidity in child population, and physical development had the trend to retardation. Meanwhile under these circumstances, the President of Russian Federation and the Government adopted regulatory documents (decrees, dedicated programs) that determined the directions of state social policy on improving the situation with children in Russian Federation until 2000.Objective. The aim of the study is to evaluate the dynamics of several medical and social indicators of 2018-2023 characterizing demographic trends direction, with proposals on improving medical care in the maternal and child health care system.Methods. The study has covered reporting form No. 19 of Russian Federal State Statistics Service (Rosstat) for children's outpatient clinics, form No. 14 for children's hospitals, form No. 030/у "Check-list of dispensary observation". The study has used the materials of the Presidential Coordination board meeting from November 15, 2016. Statistical data was obtained from the "Office of the Federal State Statistics Service for St. Petersburg and the Leningrad Region" (Petrostat) and the Center for Analysis and Forecast of Mother and Child Health at Health Committee of St. Petersburg, Medical Information and Analytical Center ("Major results in the field of health care in St. Petersburg", 2019, 2020, 2021, 2022). Statistical processing was carried out via variational statistics methods (Pearson's criterion, Fisher's angular transformation criterion) and data from the automated system of prophylactic medical examination, registration certificate FSR No. 2009/05279, corresponding to the order of the Ministry of Health of Russian Federation No. 514н dated August 10, 2017.Results. The analysis of study results confirms the negative demographic patterns in St. Petersburg like the all-Russian. Increase assisted reproductive technologies was noted alongside with birth rate decrease. There are still high rates of stillbirth and perinatal mortality, as well as increased infant mortality rate. The correlation of depopulation processes with children's health worsening and increasing disability is emphasized.Conclusion. The problems raised in this paper do not have an straightforward solution and require multimodal approach.